Russian Science Citation Index – a tool forscience analysis - P. G. Arefjev; G. O. Eremenko; V. A. Glukhov (Библиосфера)
Сurrent situation with the project on the Russian Science Citation Index (RSCI) is considered. Information on implemented and perspective developments is presented.